Listening Skills Strategies (P.I.S.A) Used in MUET: A Preliminary Study - Sulaiman, Shahirah; Ghaffar, Nur Safura Abd; Rahim, Raimizar; Majid, Azizah Abdul; Ibrahim, Mohamed Akhiruddin (International Journal of Asian Social Science, 2017)
Malaysian University English Test (MUET) has been implemented by the Ministry of Education to prepare tertiary students with the necessary English language skills. These skills are significant not just for the sake of passing the examination but also to train the students with English medium instructions in the classrooms at the tertiary level. The abovementioned skills are reading, writing, listening, and speaking; which will be examined amongst students to aid them to secure a place in universities. The four basic skills may sound manageable to learn but there are still gaps in students’ proficiency of the language which disrupt their competency, especially in their listening skills. Current researches show that students are not adequately prepared with listening strategies and listening comprehension instruction in the classroom. Thus, this study aims to investigate 60 undergraduate students’ listening strategies; P.I.S.A (Predicting, Inferring and Selective Attention), in answering their listening tasks. A quantitative approach was employed with the use of a questionnaire as the instrument. The findings confirmed that a majority of the students adopted steadily these three strategies in their listening skills. This result may help to increase the basic listening competency and cognitive abilities among the undergraduate students and thereby ultimately enhance students’ listening strategies of MUET at tertiary level.